FBXO2 promotes hepatocellular carcinoma progression and sorafenib resistance by targeting USP49 for proteasomal degradation - Hang, Sirui; Wang, Qingqing; Zhang, Jie; Dong, Yiwei; Hu, Bile; Wang, Peter; Xu, Liu (Frontiers in Immunology, 2025)
IntroductionHepatocellular carcinoma (HCC) is a highly prevalent and lethal malignancy with limited treatment efficacy due to tumor heterogeneity and the development of drug resistance. Identifying novel molecular mechanisms that drive HCC progression and therapeutic resistance is critical. F-box only protein 2 (FBXO2), an E3 ubiquitin ligase, has recently been implicated in tumorigenesis. However, its role in HCC remains unclear.MethodsWe employed CCK-8, EdU, Transwell, and wound healing assays to evaluate the functional role of FBXO2 in HCC cells. Furthermore, Western blotting, immunoprecipitation, in vivo ubiquitination assays, and cycloheximide chase analysis were conducted to investigate the molecular mechanisms through which FBXO2 contributes to tumor progression in HCC.ResultsFBXO2 is significantly upregulated in HCC tissues and correlates with poor patient prognosis. Functional assays demonstrated that FBXO2 promotes HCC cell proliferation, migration, and invasion in vitro, while its silencing exerts tumor-suppressive effects. Mechanistically, FBXO2 directly binds to and targets the USP49 for ubiquitin-mediated proteasomal degradation. This degradation decreases USP49 stability and function, thereby enhancing oncogenic potential. Importantly, silencing USP49 reversed the inhibitory effects of FBXO2 knockdown, confirming the FBXO2/USP49 axis as a functional regulator of HCC aggressiveness. Furthermore, FBXO2 depletion significantly enhanced the sensitivity of HCC cells and xenograft tumors to sorafenib treatment.ConclusionCollectively, our findings establish FBXO2 as a critical modulator of HCC progression and therapeutic resistance via USP49 degradation, highlighting FBXO2 as a promising therapeutic target for overcoming sorafenib resistance in HCC.